Lecturers’ Competencies: A Qualitatives Study in Higher Education - Samuel Anantadjaya; Irma Nawangwulan (Future Science, 2020)
The presence of well-known universities outside Indonesia has attracted sig-nificant interests, not only from Indonesian residents but also from residents of other countries. Particularly, western universities are highly demanded and the competition is rather fierce when students attempt to register and take on the entrance tests. Only the top percentile of students seems to be accepted. Because of limitations in space and personnel, those western uni-versities decided to expand their market base into developing countries by getting closer to their potential customers. With the technological advance-ment and push toward the use of the internet and online learning, undoubt-edly, international universities, including Indonesian-based universities with mixtures of curricula across countries, have become a new trend in Indone-sia’s higher educational institutions. With the growing numbers of students applying to international programs at various universities in Indonesia, it is apparent that Indonesians are more assertive to receive internationalized standards. Thus, matching consumer behaviors, and expectations in the local market would be indispensable in trying to ensure the smooth running and operational activities of the international universities in Indonesia. This pa-per attempts to focus on lecturers/professors, as the pool of human re-sources/capital in the everlasting competition within the international uni-versities in Indonesia. The focus on lecturers includes issues on human skills, ability in teaching, and teaching delivery, perhaps including research skills and research ability. It is uncertain whether the lecturers’ capacity, ability, competence, skills, knowledge, and all attributes of the lecturers to handle international classes are sufficient and fit to the consumer expectations. Re-search is conducted by gathering data from primary and secondary sources in several locations of international universities in Jakarta, such as lecturers, students, and parents. It is expected that such research would eventually the importance of lecturers’ competencies in handling international classes with international standards.